Manajemen Perpustakaan Sekolah melalui Pembentukan Tim Literasi Sekolah - Iskandar, Dede; Hidayat, Syarip; Apriliya, Seni (Universitas Negeri Padang, 2025)
This study aims to describe and analyze school library management through the formation of a school literacy team at SD Negeri 1 Cimanggu, Pangandaran. The focus of the research includes planning, organizing, implementing and monitoring school library management in an effort to improve students' literacy culture. The method used was a qualitative case study, with data collection techniques through interviews, observations and documentation studies. Research informants included the principal, librarian, teachers and members of the school literacy team. The results showed that the formation of the school literacy team plays a strategic role in optimizing library management, both in terms of services, collection procurement and maintenance, and reading habituation programs. In addition, clear coordination and division of tasks within the literacy team can create a learning environment conducive to literacy learning. The main challenges faced were limited resources and students' interest in reading, which were overcome by developing creative and innovative programs. This study concludes that school library management through the formation of a literacy team can strengthen the library's role as a learning center and build a culture of literacy in the school environment. As a recommendation, schools need to provide ongoing training and facility support for literacy teams to make library management more professional and have an impact on increasing students' reading interest and achievement.